Contribuição para o conhecimento dos Margarodinae (Homoptera, Margarodidae) que ocorrem no Brasil . - Mariconi, Francisco A. M.; Zamith, Adiel Paes Leme (Anais da Sociedade Entomológica do Brasil, 1973)
Contribution for the knowledge of Margarodinae (Homoptera, Margarodidcie) that occur in Brazil This paper deals with five species of Margarodinae, living in the soil, that are found in Brasil: Eubizococcus brasiliensis (Hempel, 1922), E. brevicornis (Silvestri, 1901), Margarodes carvahoi Costa Lima, 1949, M. paulistus Silvestri, 1939, and M. vitium Giard, 1894. A more detailed study of the species E. brasilieesis was made, and, based on the literature, the authors present some notes on distribution area, plan-hosts, bioiogy and se co for ali species above mentioned.